2020
DOI: 10.3846/tede.2020.13233
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Analysis of Environmental Efficiency From the Perspective of Environmental Regulation: Evidence From China

Abstract: The aim of this paper is to analyze the impact of environmental regulation on regional environmental efficiency convergence using the fixed effects model and threshold regression model. The results show that the differences in environmental efficiency have a convergence trend in China, as well as in the eastern, central and western regions. The effect of environmental regulation on regional environmental efficiency is inhibition first and then promotion, research and development investment and outward foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…When the compliance cost exceeds the technological innovation effect, it is not conducive to the improvement of urban eco-efficiency. The above empirical results are similar to the conclusions of Feng et al (2020), which are determined by the differences in the development stages and actual conditions of the eastern and central regions, and are also the externalization of the inherent law of regional economy.…”
Section: Heterogeneity Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…When the compliance cost exceeds the technological innovation effect, it is not conducive to the improvement of urban eco-efficiency. The above empirical results are similar to the conclusions of Feng et al (2020), which are determined by the differences in the development stages and actual conditions of the eastern and central regions, and are also the externalization of the inherent law of regional economy.…”
Section: Heterogeneity Analysissupporting
confidence: 90%
“…Wei et al (2021) found large spatial gaps in the eco-efficiency of urban clusters in China, and the differences between urban clusters are the main source of the overall gap. At the same time, environmental regulation (Feng et al, 2020), regional integration policies (Kang et al, 2022) and green technology innovation spillover (Shang et al, 2022) are the main factors which can narrow the regional eco-efficiency gap.…”
Section: Introductionmentioning
confidence: 99%
“…Research on this issue remains a relevant issue within the domain of environment, innovation, and economics [9][10][11]. To date, the majority of studies have shown that environmental oversight is the most fundamental institutional arrangement that motivates firms to fulfill their environmental responsibilities [12,13]. Theories regarding the influence of environmental oversight on pollution fall into two broad categories based on various economic theories.…”
Section: Literature Reviewmentioning
confidence: 99%